Case Report: Chimeric Antigen Receptor T Cells Induced Late Severe Cytokine Release Syndrome - He, Jinping; Xu, Na; Zhou, Hongsheng; Zhou, Ya; Wu, Di; Zhao, Ruochong; Lin, Tong; Xu, Ju; Cao, Rui; Li, Peng; Liu, Qifa (Frontiers in Oncology, 2022)
Objective: Severe cytokine release syndrome (sCRS) has emerged as an adverse complication in the early period of chimeric antigen receptor T cell (CART) therapy, while whether sCRS occurs in the late period remains unknown. Here, we aimed to elucidate the characterization of patients with late sCRS. Design: Patients diagnosed with relapsed or refractory B-cell malignancies were given fludarabine combining cyclophosphamide for lymphodepletion chemotherapy followed by CART. CAR-T cells in peripheral blood were monitored by quantitative PCR or flow cytometry. CRS was prospectively evaluated using the Penn criteria and reconciled with ASTCT CRS consensus grading system. Results: Patient one was administrated with CAR19/22 T-cell cocktail therapy and patient two received BCMA-targeted CART (BCMA-CART) therapy, respectively. 41 days and 163 days after CART infusion, two patients developed grade III CRS with the evidence of the CART remarkable re-expansion. Conclusion: Severe CRS could occur in the late period after CAR-T therapy as re-expansion of CAR T-cells possessed the potential risk for late sCRS.